PROFIL KEMAMPUAN BAHASA INGGRIS MAHASISWA STKIP PGRI SIDOARJO BERDASARKAN GAYA BELAJAR - endang wahju andjariani (LPPM STKIP PGRI Sidoarjo, 2018)
Learning style of everyone can be a factor to the people to have different understanding competency about information. One of this is English and it can be different for everyone. The goal of this research was to describe English competency of 62 mathematical students by their learning style using questioner of learning style and TOEP. The result shown that there were seven type of learning style: auditory, kinesthetic, visual, auditory-kinesthetic, auditory-visual, kinesthetic-visual, and auditory-kinesthetic-visual that all of them have good listening competency than another.